Duta Perilaku Hidup Bersih Dan Sehat (PHBS) Sebagai Kader Perilaku Hidup Bersih Dan Sehat Pada Siswa SDN 1 Bajur Labuapi Lombok Barat - Zulkahfi, Zulkahfi; Hadi, Irwan; Halid, Sopian; Maliki, Imam (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Clean and healthy living behavior (PHBS) in school is a set of behaviors that are practiced by students, teachers, and the school environment community on the basis of awareness as a learning result, so that they are independently able to prevent diseases, improve their health, and play an active role in realizing a healthy environment. Based on the results of the previous study, it was shown that out of 56 respondents there were 25 people (44.5%) who washed their hands with soap and water, 35 respondents (62.5%) ate enough healthy food and healthy canteens, 26 people (46.4%) who did not carry out the use of clean and healthy latrines, 33 people (59%) did not throw garbage in its place, 34 people (30.7%) who did not carry out regular and measurable exercise, 24 people (42.8%) did not carry out mosquito larvae eradication, 27 people who smoked (48.2%) and 23 people (41.1%) did not carry out weight and height weighing. Based on the results of the study, it shows that there is still a lack of implementation of PHBS at SDN 1 Bajur, this is due to the lack of student awareness and the availability of health facilities and infrastructure is still minimal, besides that there is still a lack of health education and health services provided by teachers, especially at school. Based on this, it is necessary to carry out Community Service about healthy living behaviors and the formation of PHBS Ambassadors as PHB Cadres for Students at SDN 1 Bajur Labuapi West Lombok. The results of the service were obtained that this community service activity consisted of health counseling and cadre training. The training of health cadres of SDN 1 Bajur Labuapi Lombok with the expected outcome is the formation of PHBS Ambassadors as PHBS cadres. Based on the evaluation of PHBS Ambassadors, PHBS cadres have understood how to maintain their own health and the environment with PHBS and they have been able to manage waste well and are able to put waste according to their forging.